Exploring IT Identity Loss - A Netnographic Case Study of the Battlefield: Bad Company 2 Shutdown - Brechtelsbauer, Bastian; Schwehn, Tim-Julian (International Conference on Information Systems 2024, 2024)
Although information technology (IT) is becoming an increasingly important part of individuals’ lives, we know little about how permanent IT shutdowns affect users. Similarly, whereas previous research has investigated the significant impact of IT, e.g., video games, on users’ identities, the effects of shutting down an identity-related IT are unclear. To these ends, we employ a netnographic approach to conduct an interpretive case study of the recent shutdown of Battlefield: Bad Company 2 to examine its effects on players’ identities. Based on our empirical findings, we introduce the novel concept of IT Identity Loss to capture various forms of identity loss that can result from the removal of identity-forming IT. Additionally, we discuss possible reactions to IT Identity Loss. Thereby, our research contributes to the literature on identity and IT, and IT shutdowns, specifically of video games. Finally, we outline implications for players and publishers, and plans for further investigations. <
Keywords: Identity; IT Identity Loss; IT Identity; Video Games; Shutdown